Sustainability reporting at a crossroads in Italian universities: Is web-based media adoption deinstitutionalising sustainability reporting? - Patrizia Di Tullio; Matteo La Torre (Administrative Sciences, 2022)
Higher education institutions and universities have recently started to publish their sustainability and corporate responsibility reports. Yet, due to digitalisation and the benefits of digital reporting, websites offer organisations novel opportunities to communicate more updated, timely and interactive information than a periodic sustainability report. However, we know little about sustainability reporting practice within universities and their use of online communication. This study examines the relationship between sustainability reporting practices and web-based communication practices in Italian universities. We employed a qualitative enquire and content analysis of the sustainability web pages of Italian public universities by analysing their content and updates and their relationship with their adoption of sustainability reporting. Our results suggest there are risks to web-based media being used to replace sustainability reporting, resulting in a deinstitutionalising effect for sustainability reporting. This study contributes to the literature on sustainability reporting and disclosure in universities by exploring web-based university communication on sustainability issues and stimulating the debate on replacing sustainability reports with more timely and interactive forms of communication.
Keywords: 350; deinstitutionalisation; Italian public universities; public sector; sustainability; sustainability reporting; sustainability web pages; universities